Improving Critical Thinking Skills in Writing Essay - Wanawir Abdul Muin; Lisdwiana Kurniati (Peneliti.net, 2022)
This study aims to determine the effect of critical thinking on the use of students' critical thinking skills in essay writing. This study uses an experimental study conducted on Indonesian students from the Department of Informatics Engineering divided equally into the experimental group and the control group. While participants in the experimental group were taught to write with critical thinking skills, others were taught to write without reference to these skills. Participants in both groups took a pre-test and posttest to evaluate the development of their use of critical thinking skills in argumentative writing. Data that has been analyzed quantitatively shows that the experimental group significantly outperformed the control group. The students' ability to use more credible evidence, answer alternative arguments, support conclusions, and maintain a logical flow of ideas in their essays did not reach the level of mastery in the posttest, but the average level they achieved was convincing considering the short training time they had. Critical Thinking integration for a longer time can yield satisfactory results.